TRANSFORMASI KEBIJAKAN KEIMIGRASIAN DALAM ERA DIGITAL: STUDI KASUS SISTEM E-VISA DI INDONESIA: TRANSFORMATION OF IMMIGRATION POLICY IN THE DIGITAL ERA: A CASE STUDY OF THE E-VISA SYSTEM IN INDONESIA - Mas’adi, Daffa Raihan Arya; Bawono, Sri Kuncoro; Ryanindityo, Mochammad (Journal of Administration and International Development, 2025)
Abstract. : Digital transformation in immigration policy is the main focus in increasing the efficiency and transparency of public services in Indonesia. One significant innovation is the implementation of the e-Visa system, which allows applicants to apply for visas online without the need for face-to-face interaction. This research uses a qualitative approach with a case study method to analyze the implementation of the e-Visa system in Indonesia. Data was collected through literature studies, analysis of official documents, as well as in-depth interviews with immigration officials and e-Visa service users. The analysis was carried out thematically to identify the benefits, challenges and impacts of digitalization on immigration, tourism and investment. The research results show that e-Visa is able to speed up the administration process, increase tourism competitiveness, and reduce complex bureaucracy. However, the main challenges include issues of data security, technological infrastructure readiness, and community digital literacy. To optimize the implementation of e-Visa, strong regulations are needed, improving cyber security systems, as well as collaboration between the government and the private sector in providing digital infrastructure. Keywords: e-Visa, Immigration Digitalization, Policy Transformation, Public Services, Data Security, E-Government, Case Studies Abstrak. Transformasi digital dalam kebijakan keimigrasian menjadi fokus utama dalam meningkatkan efisiensi dan transparansi layanan publik di Indonesia. Salah satu inovasi signifikan adalah implementasi sistem e-Visa, yang memungkinkan pemohon mengajukan visa secara daring tanpa perlu interaksi tatap muka. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus untuk menganalisis penerapan sistem e-Visa di Indonesia. Data dikumpulkan melalui studi literatur, analisis dokumen resmi, serta wawancara mendalam dengan pejabat imigrasi dan pengguna layanan e-Visa. Analisis dilakukan secara tematik untuk mengidentifikasi manfaat, tantangan, serta dampak digitalisasi terhadap keimigrasian, pariwisata, dan investasi. Hasil penelitian menunjukkan bahwa e-Visa mampu mempercepat proses administrasi, meningkatkan daya saing pariwisata, serta mengurangi birokrasi yang kompleks. Namun, tantangan utama meliputi isu keamanan data, kesiapan infrastruktur teknologi, serta literasi digital masyarakat. Untuk mengoptimalkan implementasi e-Visa, diperlukan regulasi yang kuat, peningkatan sistem keamanan siber, serta kolaborasi antara pemerintah dan sektor swasta dalam penyediaan infrastruktur digital. Kata Kunci: e-Visa, Digitalisasi Keimigrasian, Transformasi Kebijakan, Layanan Publik, Keamanan Data, E-Government, Studi Kasus